Making Video Animations with Daily Life and Family Themes for Hören A1 - Cinta Caroline Hasian Pardede; Ahmad Bengar Harahap (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to create an animated video with the topic